Trends in Up-To-Date Colorectal Cancer Screening Among U.S. Adults Aged 50-75 Years and Variations by Race/Ethnicity and U.S. Census Bureau Divisions - Itunu O. Sokale, MBBS, DrPH; Omar Rosales, MPH; Jane R. Montealegre, PhD; Abiodun O. Oluyomi, PhD; Aaron P. Thrift, PhD (Elsevier, 2023)
Introduction: Mortality rates from colorectal cancer have declined over the past decades owing to population-based life-saving screening interventions. However, screening inequalities continue among racial and ethnic minorities despite having a higher disease burden. In this study, we assessed the patterns of up-to-date colorectal cancer screening rates among racial/ethnic groups across the U.S. Census Bureau Divisions. Methods: This population-based cross-sectional study used weighted data from 4 cycles of the Behavioral Risk Factors Surveillance System (2014, 2016, 2018, and 2020) of adults aged 50‒75 years without a previous diagnosis of colorectal cancer. The primary outcome was guideline-recommended up-to-date colorectal cancer screening. We used logistic regression models to examine temporal trends in up-to-date colorectal cancer screening from 2014 to 2020. In addition, we conducted detailed descriptive statistics of up-to-date screening rates, comparing trends in 2020 with those in 2014 overall by race/ethnicity and U.S. census divisions. Results: The overall proportion of individuals with up-to-date colorectal cancer screening increased from 66.5% in 2014 to 72.5% in 2020 (p<0.001). For racial/ethnic subgroups, from 2014 to 2020, screening rates increased significantly among non-Hispanic Whites (68.5%‒74.5%, p<0.001), non-Hispanic Blacks (68.0%‒74.6%, p<0.001), and Hispanics (51.5%‒62.8%, p<0.001). However, increases were not observed in all U.S. Census Bureau Divisions. Conclusions: Although colorectal cancer screening rates improved over time, they fall short of the 80% target. Substantial racial/ethnic and geographic disparities remain. Future studies investigating the factors influencing these disparities are needed.